2002
DOI: 10.1024/0300-9831.72.2.91
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin C and Vitamin E on Lipid Peroxidation Status, Serum Hormone, Metabolite, and Mineral Concentrations of Japanese Quails Reared under Heat Stress (34º C)

Abstract: This study was conducted to determine the effects of dietary vitamin C (L-ascorbic acid) and vitamin E (alpha-tocopherol acetate) on lipid peroxidation status measured as MDA and serum triiodothyronine (T3), thyroxine (T4), thyroid-stimulating hormone (TSH), adrenocorticotropic hormone (ACTH), as well as some other serum metabolite and mineral concentrations of Japanese quails reared under heat stress (34 degrees C). One hundred-eighty 10-day-old Japanese quails were randomly assigned to six treatment groups, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
81
2
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(101 citation statements)
references
References 26 publications
(39 reference statements)
15
81
2
3
Order By: Relevance
“…The lower plasma corticosterone concentration in hens was probably due to various anti-stress effect mecha-nisms of the arginine and vitamin C combination (Bozakova & Gerzilov, 2014). Apart the discussed inhibiting role of arginine metabolite on ACTH and corticosterone secretion, vitamin C further reduces corticosterone levels by participating in gluconeogenesis during stress (Jones et al, 1996;Sahin et al, 2002). This way the results of the present experiment provide evidence for the synergistic activity of L-arginine and vitamin C for heat stress reduction and poultry welfare improvement.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…The lower plasma corticosterone concentration in hens was probably due to various anti-stress effect mecha-nisms of the arginine and vitamin C combination (Bozakova & Gerzilov, 2014). Apart the discussed inhibiting role of arginine metabolite on ACTH and corticosterone secretion, vitamin C further reduces corticosterone levels by participating in gluconeogenesis during stress (Jones et al, 1996;Sahin et al, 2002). This way the results of the present experiment provide evidence for the synergistic activity of L-arginine and vitamin C for heat stress reduction and poultry welfare improvement.…”
Section: Discussionsupporting
confidence: 57%
“…Sahin et al (2002) found that in Japanese quails subjected to heat stress, the supplementation of 250 mg/kg vitamin C lowered blood ACTH concentrations. McDowell (1989) affirmed that vitamin C alleviated the negative effects of stress by decreasing the synthesis and secretion of corticosteroids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, overall serum Zn concentration was significantly high in the vitamin E fed group compared to control. In support to our study, Sahin et al (2002) found that three levels of vitamin E (125, 250 and 500 mg/kg) significantly increased egg yolk Zn concentration in laying Japanese quails. In another study, Sahin et al (2003) documented that vitamin E increases the retention of Zn, and decreased its secretion from the body of Japanese quails, when they were supplemented 250 mg/kg vitamin E. Zn plays a very important role in the anti-oxidant defence system of the body, and its deficiency has been linked with oxidative damage of the cell membrane leading to oxidative stress (Salgueiro et al 2000;Prasad & Kucuk 2002).…”
Section: Discussionsupporting
confidence: 76%
“…Sahin et al (2003b) and Khan et al (2014b) reported that vitamin E supplementation increased serum concentration of Zn in birds subjected to various kinds of stresses. Sahin et al (2002) concluded that vitamin E supplementation at various levels (125, 250, and 500 mg/kg) increased significantly the Zn concentration in the egg yolk in laying Japanese quail. Environmental stress has been found to reduce the concentration of certain vitamins and minerals (Khan et al, 2014a(Khan et al, , 2014b.…”
Section: Discussionmentioning
confidence: 99%